Educational intervention through a comic book for preoperative anxiety in children, adolescents, and their parents: A randomized clinical trial - Garcia De Avila, Marla Andréia [UNESP]; Prata, Rafaela Aparecida [UNESP]; Jacob, Francine Letícia Da Silva [UNESP]; Nóbrega, Francisca Miriam De Oliveira; De Barros, Gabriela Ribeiro [UNESP]; Sugiura, Beatriz Mayumi Gonsales [UNESP] (Elsevier, 2022)
Background: Reducing preoperative anxiety can help optimize surgical care. Aim: To analyze the effectiveness of verbal guidance by nurses versus verbal guidance combined with a comic book on preoperative anxiety in children and their parents. Methods: We conducted a randomized parallel, two-group controlled clinical trial in the pediatric ward and a blinded anxiety assessment in the operating room of a Brazilian hospital. Individuals aged 6–14 years undergoing surgical procedures of up to 4 h for the first time were included in the study. Parents who were adults, literate, and able to communicate verbally were included. The primary outcome was the children's anxiety, measured by the Children Anxiety Questionnaire (CAQ), Visual Analog Scale (VAS), and the modified Yale Preoperative Anxiety Scale (mYPAS); the secondary outcome was the parents' anxiety, assessed by the Hamilton Anxiety Rating Scale. Participants were divided into the intervention (IG; n = 60) and control (CG; n = 60) groups. Findings: The two groups were homogeneous. The median age of the children was 8 years. No significant differences were observed in the CAQ and VAS scores between the two assessment time points or in the mYPAS scores between the IG and CG. However, parents' anxiety significantly decreased in both groups. Application to practice: Preoperative guidance by nurses, either verbal only or verbal information with a comic book proved beneficial in reducing parental anxiety. However, both interventions, performed on the day of surgery, failed to reduce preoperative anxiety in children and adolescents upon admission to the operating room. We recommended the process of preparing the child should begin after scheduling the surgery.
Keywords: Clinical trial; Patient education handout; Pediatric nursing; Perioperative nursing; Surgery